2005
DOI: 10.1007/s10534-004-5789-1
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of insulinoma cells to cadmium and modulation by L-type calcium channels

Abstract: Cadmium (Cd), a toxic metal that induces apoptosis and necrosis in a variety of cells, accumulates in pancreas and may be a cause of diabetes in humans. In the insulinoma cells line HIT-T15 (HIT), we measured internal calcium (Ca) and Cd levels by the fluorescent dye Fura-2 and confirm that L-type voltage-dependent calcium channels (VDCC) play a major role in glucose response and represent a pathway of Cd influx in these cells. Therefore we examined the role of VDCC in acute Cd poisoning by comparing its accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
3
9
0
Order By: Relevance
“…VDCCs mediate Cd influx in excitable cells [15–18], including mammalian neurons [19], and have been proposed to participate in Cd uptake also in cells from nonexcitable tissues [20]. In a previous work of my laboratory, we showed that in certain cells Cd permeation occurs mainly through VDCC of the L-type [19, 21]. However, in other studies, the presence of VDCC per se did not seem to enhance sensitivity to Cd; for example, VDCCs expressing (PC12) and nonexpressing (PC18) cells showed comparable LD 50 for Cd [18], and the role of this pathway in the induction of cell death appears questionable.…”
Section: Introductionmentioning
confidence: 99%
“…VDCCs mediate Cd influx in excitable cells [15–18], including mammalian neurons [19], and have been proposed to participate in Cd uptake also in cells from nonexcitable tissues [20]. In a previous work of my laboratory, we showed that in certain cells Cd permeation occurs mainly through VDCC of the L-type [19, 21]. However, in other studies, the presence of VDCC per se did not seem to enhance sensitivity to Cd; for example, VDCCs expressing (PC12) and nonexpressing (PC18) cells showed comparable LD 50 for Cd [18], and the role of this pathway in the induction of cell death appears questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Such interpretation is strongly supported by the results obtained by many groups which reported the induction of apoptosis after Cd or Zn treatments in pancreatic cells as well as in several other cell lines at similar, or identical, metal concentrations (De la Fuente et al, 2002;Gavazzo et al, 2005;Koh, 2001;Pathak and Khandelwal, 2006;Watjen and Beyersmann, 2004;Wiseman et al, 2006).…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, recent findings (Priel and Hershfinkel, 2006) indicate that such safety systems are unable to respond efficiently in the presence of higher (close to 100 lM), non physiological, concentration of Zn which is still capable of triggering the cell damage. On the other hand, both Zn and Cd ions can cross the membrane of insulinoma cells through the voltage-dependent Ca channels and, in particular, the induction of apoptosis by 100 lM of Cd has been recently demonstrated (Gavazzo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Using the insulinoma cell line, HIT-T15, Cd accumulation was significantly greater when cells were depolarized in a 20 mM KCl solution. In the presence of the L-type Ca channel inhibitor, nimodipine, Cd accumulation was significantly less [44]. In the same study, nimodipine reduced apoptotsis in HIT-T15 cells exposed to Cd.…”
Section: Mechanims Of Cadmium-mediated Hyperglycemia / T2dmmentioning
confidence: 91%